"Internet + Special Agriculture" Drives Rural Green Revitalization - Investigation and Analysis of Xunwu County, Jiangxi Province - Zhou, Shixiong; Huang, Liang (International Journal of Emerging Trends in Social Sciences, 2020)
"Internet + agriculture” organically combines Internet technology with traditional agriculture to achieve agricultural transformation and upgrading. Under the strategy of rural rejuvenation, Xunwu County, Jiangxi Province, developed "Internet + characteristic agriculture" according to local conditions, which has optimized the local agricultural scale and characteristic agricultural formats. However, the "Internet + characteristic agriculture" in Jiangxi Province still has problems such as imbalanced structural development, low level of inclusive finance, and insufficient professional talent reserves. It is necessary to promote the industrial and financial development of various agricultural sectors and the Internet, increase policy support for talents to return to their hometowns to start businesses, promote the popularization of Internet finance in rural areas, and adjust the agricultural product trade structure to achieve the common development of various types of crops.